PRACTICAL METHODS OF SERVICE QUALITY MANAGEMENT IN ESTABLISHMENTS OF RESTAURANT INDUSTRY - Kucher, M. M.; Korneyev, M. V.; Shcholokova, H. V.; Stepaniuk, B. V. (Systems and Technologies, 2026)
The article systematises practical methods of managing service quality in restaurant industry establishments (RIEs). Tools for analysing situations and developing ideas for improving quality are identified. Recommendations are provided on selecting the most favourable ideas for this sector. It is established that improving and ensuring service quality are key tasks for restaurant management. Quality management as a direction of activity of RIEs is carried out to improve services continuously and the mechanisms of enterprise activity as well as bring products and services into line with standards. The essence of the concept of “service quality management” in the context of restaurant activity is shown, its components and specifics of assessment are outlined. It has been found that effective quality management requires a comprehensive approach that includes standardisation of service processes, continuous monitoring of customer satisfaction, staff training and the introduction of innovative technologies. Among the tools that determine practical quality management methods, the tools of control, analysis, design, and management are highlighted. The work is the quintessence of the results of research on the practice of functioning of RIEs. Attention is focused on practical methods and analytical tools that allow negative trends emerging in the activities of RIEs to be identified. In order to identify problem areas in the activity of establishments, it is recommended to conduct a self-assessment using various assessment methods and digital technologies to collect and analyse feedback. Based on the study of the experience of RIEs, the factors that form the quality of restaurant services are characterised. Goals for improving service quality are formulated. It has been established that if measures aimed at continuous and gradual improvement of service quality are insufficiently effective (or lose their effect), it is advisable to resort to a policy of breakthrough improvements. The practical significance lies in the formulation of recommendations for improving quality management efficiency for managers of RIEs in order to strengthen competitive positions and customer loyalty. The results can be used in the practical activity of RIEs seeking to achieve high standards of service.